2003
DOI: 10.1177/194589240301700604
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Treatment of the Nasal Inverted Papilloma

Abstract: According to the literature and our own experience, we believe that the initial surgical management of primary and recurrent inverted papillomas limited to the nasal cavity and paranasal sinuses should be endoscopic sinus surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 15 publications
2
22
0
Order By: Relevance
“…Pasquini et al [11] reported lower recurrence rate of 3% with endoscopic procedure and 24% with traditional approaches. Endoscopic approaches have low recurrence rate as also evidenced by other studies [11][12][13]. If inverted papilloma involves inferomedial wall of frontal sinus, modified Lothrop procedure should be done, whereas in cases of lateral or more superior involvement of the frontal sinus, an osteoplastic flap may be additionally needed to gain adequate exposure [7].…”
Section: Discussionmentioning
confidence: 89%
“…Pasquini et al [11] reported lower recurrence rate of 3% with endoscopic procedure and 24% with traditional approaches. Endoscopic approaches have low recurrence rate as also evidenced by other studies [11][12][13]. If inverted papilloma involves inferomedial wall of frontal sinus, modified Lothrop procedure should be done, whereas in cases of lateral or more superior involvement of the frontal sinus, an osteoplastic flap may be additionally needed to gain adequate exposure [7].…”
Section: Discussionmentioning
confidence: 89%
“…Whether traditional open surgical approaches afford any advantage in this respect when compared with modern endoscopic techniques is a subject of controversy. A number of series [3][4][5][6][7] have been reported in the literature in the past 5 years demonstrating the feasibility of endoscopic resection with long-term follow-up. A particularly large series of 160 patients reported by Lawson et al in 2003 [8] demonstrated a low recurrence rate (12%) for endoscopic procedures performed when the inverted papillomas originated from the ethmoid, sphenoid, or medial wall of the maxillary sinus.…”
Section: Surgical Management Of Inverted Papillomamentioning
confidence: 98%
“…There is little consensus regarding the incidence or role of Epstein-Barr virus (EBV) in IP [119, 120] which is further questioned by other studies [121, 122]. Human papilloma virus (HPV) infection is responsible for 15 to 35 percent of head and neck cancers worldwide [123–130].…”
Section: Etiology and Pathogenesismentioning
confidence: 99%
“…Significant association has been identified between the presence of human papilloma virus DNA in inverted papilloma and recurrence after surgical excision [144, 147, 148]. Some authors argued against the role of HPV in the pathogenesis of exophytic papilloma while others denied its association with developing malignancy and recurrence [121, 149151]. HPV serotypes 6 and 11 are associated with the fungiform papilloma, and to a lesser degree, with inverted papillomas [37, 120, 152156].…”
Section: Etiology and Pathogenesismentioning
confidence: 99%